Strategy for the Development of Sustainable Vannamei (Litopenaeus vannamei) Shrimp Culture in Plastic Ponds in Tegal Regency, Central Java - Purwanto Purwanto; Sarjito; Dian Wijayanto (Department of Aquaculture, 2023)
Vannamei shrimp culture is a fishery sub-sector that is being promoted by the Indonesian government. The vannamei shrimp culture great bussiness prospect makes many farmers to carry out these business activities. However, if the culture business is carried out in an environmentally unfriendly way, the sustainability of the business will stop. The purpose of this study is to determine the correct strategy for the development of vannamei shrimp culture in plastic ponds in Tegal Regency, Central Java. The research method used is the survey method with purposive sampling, the respondent sampling technique is non probability sampling and data collection with interviews, questionnaires, observation and documentation. The data obtained were analyzed descriptively and SWOT. The number of respondents was 38 people. The results indicated that the production of vannamei shrimp has decreased in the last three years due to Acute Hepato Pancreatic Necrosis Disease outbreak. A calculation matrix factor strategy internal (IFAS), strength (S) biggest are good and correct culture SOPs (0.349) and the calculation of the external strategy matrix (EFAS), opportunities (O) the largest is the large market goose p (0,293). Relationship factor occupy cell V, from effort the describe the situation growth and stability which means that the business is in a relatively stable condition and growth is likely to occur. Based on the SWOT analysis, the ranking of alternative strategies obtained is the SO strategy (Strengths – Opportunities) with total score of 3,602. Priority alternative strategy which used is optimizing the quality and quantity of products by using good and correct SOP, using technology, available infrastructure and availability of adequate seeds to produce quality and quantity of products so that continuity is maintained, so as to meet high market and consumer demand.